Project-Based Curriculum in Rows and Rows to Improve Critical Thinking of Students - Ainul Marhamah Hasibuan; Emilda Sulasmi (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
This study aims to analyze the implementation of a project-based learning (PjBL) curriculum in mathematics learning on sequences and series to improve students' critical thinking skills. The method used was a literature review with a qualitative descriptive approach. The results showed that the implementation of PjBL can improve students' critical thinking, problem-solving, and 21st-century skills. PjBL provides contextual learning experiences through real-life projects, enabling students to actively construct knowledge. Learning about sequences and series related to everyday life has been proven to be more effective than conventional learning.